Adolescent psychological distress, unemployment, and the Great Recession: Evidence from the National Longitudinal Study of Youth 1997. (May 2016) - Egan, Mark; Daly, Michael; Delaney, Liam
Abstract: Rationale: Several studies have shown a link between psychological distress in early life and subsequent higher unemployment, but none have used sibling models to account for the unobserved family background characteristics which may explain the relationship. Objective: This paper uses the National Longitudinal Study of Youth 1997 data to examine whether adolescent psychological distress in 2000 predicts higher unemployment over 2000–11, whether this relationship changed in the period following the Great Recession, and whether it is robust to adjustment for family effects. Methods: 7125 cohort members (2986 siblings) self-reported their mental health in 2000 and employment activities over 2000–11. This association was examined using Probit and ordinary least squares regressions controlling for intelligence, physical health, other sociodemographic characteristics and family background. Results: After adjustment for covariates and compared to those with low distress, highly distressed adolescents were 2.7 percentage points (32%) more likely to be unemployed, 5.1 points (26%) more likely to be unemployed or out of the labor force and experienced 11 weeks (28%) more unemployment. The impact of high distress was similar to a one standard deviation decrease in intelligence, and double the magnitude of having a serious physical health problem, and these estimates were robust to adjustment for family fixed-effects. The highly distressed were also disproportionately more likely to become unemployed or exit the labor force in the years following the Great Recession. Conclusion: These findings provide strong evidence of the unemployment penalty of early-life psychological distress and suggest that this relationship may be intensified during economic recessions. Investing in mental health in early life may be an effective way to reduce unemployment. Highlights: Highly distressed adolescents were at higher risk of unemployment as adults. This elevated risk of unemployment was accentuated during the Great Recession. Risk similar to effect of 1 SD decrease in intelligence, robust to sibling fixed-effects. Investment in adolescent mental health could reduce future unemployment.